Intended to Fail: The Problems of Regulating and Reviewing Discretion in Indonesia (An Empirical Study) - Despan Heryansyah; Desmalinda (Universitas Muhammadiyah Ponorogo, 2026)
In accordance with the principle of the rule of law (rechtstaat), all legal actions (rechtshandelingen) and/or factual actions (feitelijke handelingen) of government officials must be based on applicable laws and regulations. However, the increasing complexity of societal life means that not all public affairs are fully regulated. Existing regulations often contain vague or open norms that provide room for interpretation, thereby requiring the exercise of administrative discretion. While discretion is necessary to ensure effective governance, its use without clear requirements, objectives, and limitations may lead to arbitrary actions that harm the public, particularly when there is limited legal space to challenge or annul such decisions. To address this issue, Law Number 30 of 2014 on Government Administration establishes provisions regarding the requirements, procedures, objectives, and review mechanisms for government discretion. Nevertheless, the regulatory framework still contains several ambiguities, resulting in practical difficulties and uncertainty for government officials in exercising discretion as well as for judges of the Administrative Court (PTUN) in reviewing disputed discretionary decisions.